Research on China's Environmental Governance Mode: Quality Driven or Quantity Driven? - Ma, Yubin; Chen, Haotian; Zhao, Yating; Li, Zhengda (Frontiers in Environmental Science, 2022)
High-quality environmental governance (EG) is closely related to its governance model. Nevertheless, few studies have examined the EG model from the dual perspectives of quality and quantity. This paper utilizes panel data of 30 Chinese provinces from 2003-2020 to research the influence of environmental governance efficiency (EGE) and investment (EGI) on EG through a fixed-effect model. The outcomes show that China's EG is driven mainly by quantitative EGI. EGE and EGI show significant geographic regions, economic development levels, resource endowments, and stage heterogeneity to EG. In light of these conclusions, this article argues that the future needs to reasonably allocate EGI based on consideration of the heterogeneity of geographical regions, economic development levels and resource endowments to optimize EGI structure and increase EGE in each province to achieve high-quality EG.